2012
DOI: 10.1073/pnas.1201132109
|View full text |Cite
|
Sign up to set email alerts
|

TWIK1, a unique background channel with variable ion selectivity

Abstract: TWIK1 belongs to the family of background K + channels with two pore domains. In native and transfected cells, TWIK1 is detected mainly in recycling endosomes. In principal cells in the kidney, TWIK1 gene inactivation leads to the loss of a nonselective cationic conductance, an unexpected effect that was attributed to adaptive regulation of other channels. Here, we show that TWIK1 ion selectivity is modulated by extracellular pH. Although TWIK1 is K + selective at neutral pH, it becomes permeable to Na + at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
131
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(142 citation statements)
references
References 31 publications
10
131
1
Order By: Relevance
“…3, C-E). A most recent publication reported that the TWIK-1⅐K274E⅐I293A⅐I294A mutant (TWIK-1 surf ) channels heterologously expressed in Xenopus oocytes, which largely increase detectable TWIK-1 currents, exhibit altered ion selectivity in lowered pH o (35). However, whether TWIK-1 surf channels represent TWIK-1 wild type K ϩ channels is questionable in terms of ion selectivity because the data presented in the study showed that TWIK-1 surf channels are K ϩ -selective in pH 7.4 Na ϩ -based bath solutions with 0 and 2 mM K ϩ , not consistent with previous observations that TWIK-1 wild type channels are nonselective channels significantly permeable to extracellular Na ϩ in 0 and 2 mM [K ϩ ] o (19,32).…”
Section: Dynamic Ion Selectivity Of Acid-sensitive Twik and Task Kmentioning
confidence: 99%
“…3, C-E). A most recent publication reported that the TWIK-1⅐K274E⅐I293A⅐I294A mutant (TWIK-1 surf ) channels heterologously expressed in Xenopus oocytes, which largely increase detectable TWIK-1 currents, exhibit altered ion selectivity in lowered pH o (35). However, whether TWIK-1 surf channels represent TWIK-1 wild type K ϩ channels is questionable in terms of ion selectivity because the data presented in the study showed that TWIK-1 surf channels are K ϩ -selective in pH 7.4 Na ϩ -based bath solutions with 0 and 2 mM K ϩ , not consistent with previous observations that TWIK-1 wild type channels are nonselective channels significantly permeable to extracellular Na ϩ in 0 and 2 mM [K ϩ ] o (19,32).…”
Section: Dynamic Ion Selectivity Of Acid-sensitive Twik and Task Kmentioning
confidence: 99%
“…However, in endogenous systems, expression of TWIK-1 has been documented in various tissues, including the brain, heart and kidney 3 . Mice deficient in TWIK-1 show defects in phosphate transport in the proximal tubule and water transport in the medullary collecting duct of kidney, as well as deviations in the resting membrane potential of pancreatic b cells 4,5 . In addition, it has been recently reported that TWIK-1 conducts inward leak Na þ currents during pathological hypokalaemia in cardiomyocytes 6 .…”
mentioning
confidence: 99%
“…1A). Hysteresis of ion channels is linked to an ever-growing number of human physiological processes, among them normal heartbeat (2), stable rhythmic firing of pacemaking neurons, synaptic integration (3), regulation of cell excitability (4,5), and temperature sensitization of transient receptor potential channels (6,7).…”
mentioning
confidence: 99%